Induction of phosphoribomutase in Bacillus cereus growing on nucleosides - Ipata, Pier Luigi; Sgarrella, Francesco; Catalani, Roberta; Tozzi, Maria Grazia (Biochimica et biophysica acta, 1983)
In this paper we show that phosphoribomutase is induced in Bacillus cereus by the same metabolizable purine and pyrimidine ribonucleosides previously shown to induce the purine nucleoside phosphorylase (Tozzi, M.G., Sgarrella, F. and Ipata, P.L. (1981) Biochim. Biophys. Acta 678, 460–466). The mutase allows ribose 1-phosphate formed from nucleosides to be utilized by the cell through the pentose cycle, upon transformation to ribose 5-phosphate. The equilibrium constant of the mutase reaction is towards ribose-5-phosphate formation. The coordinate induction of the two enzymes completes the picture of the molecular events leading to the utilization of the sugar moiety of purine nucleosides and nucleosides as an energy source (Mura, U., Sgarrella, F. and Ipata, P.L. (1978) J. Biol. Chem. 253, 7905–7909).